The origins of Islamist insurgencies: the social-institutional foundations of an ideological shift - Naghizadeh, MH (2022)
Islamism has become the predominant ideology of civil war in the post-Cold War order, and yet its significance for civil wars remain poorly understood. At the macro-historical level, it is unclear why it was Islamism, rather than something else, which replaced socialism as the foremost counter-hegemonic ideology among Muslim would-be revolutionaries. At the micro-level, there are no satisfactory explanations for why some rebel groups adopt Islamist ideology while others do not. This thesis is an attempt at theory-building to explain the historical rise of Islamism among rebel groups, through an inductively-derived theory of how group-ideology is determined by the process of mobilisation at the micro-level.